PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN CROSSWORD PUZZLE TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VIII MTsN 7 PADANG - Melin Wirman; Febri Yanto; Aulia Azhar; Ade Sazaliana (STKIP Subang, 2026)
The low learning outcomes of students in science subject are mainly caused by conventional learning models and limited instructional media, resulting in minimal student interest, motivation, and participation. This study aims to examine the effect of the Problem Based Learning model assisted by Crossword Puzzle on the learning outcomes of eighth-grade students at MTsN 7 Padang. This research uses a quantitative approach with a quasi-experimental method and a non-equivalent control group design. The sample was selected through purposive sampling, with class VIII.1 as the experimental group and class VIII.2 as the control group. Data were collected through outcome tests pretest and posttest using multiple-choice items, observation sheets, and student response questionnaires, analyzed using Microsoft Excel. The findings show that learning implementation reached 98% for teacher activities and 93% for student activities, both categorized as very good. The average posttest score of the experimental group 87.86 was higher than the control group 63.45. Hypothesis testing showed t​hitung 7.037 > ttabel 2.004, leading to the rejection of H0. Student responses were positive, at 71.35%, categorized as good. These results show that the Problem Based Learning model assisted by Crossword Puzzle significantly affects the learning outcomes of eighth-grade students at MTsN 7 Padang.